(untitled) (Bioagro, 2025)
Moniliasis in cocoa is considered the main phytosanitary factor limiting production in the producing areas of Latin America. Evaluate the application of mixed agricultural alternatives in the agroecological management of this disease in cultivation. The study was conducted in the Gavilanes Panamericana sector, municipality Obispo Ramos de Lora of the state of Mérida, Venezuela, on plants 3 years old; using a completely random design, establishing seven treatments, 1: Trichoderma harzianum, 2: Maintenance and sanitary pruning; 3: Humato, 4: T. harzianum + Maintenance and sanitary pruning; 5: Humato + Maintenance and sanitary pruning; 6: Humato + T. harzianum and T7: Absolute control in batches of five cocoa trees and three repetitions, for a total of 105 experimental units. The pathometric indices were evaluated: incidence of disease (IE), external severity index (ISE) and internal in fruit (ISI) and for the records of effect on yields was determined the weight of the almond in dross (PAB).IE was lower in all alternative treatments than in the control, with a remarkable use of maintenance and sanitary pruning at an index of 22.87 %. Humato applications showed a significant reduction in the ISE of 1,86 to 0,80 degrees compared with the increase in the same time range to 3,60 in control. Use of Trichoderma harzianum reduced the ISI of the disease in the fruit from grade 5 (from 61 to 80% damage) to 2 (from 1 to 20% damage). Finally, the applications of pruning and the use of T. harzianum were the treatments that showed the greatest increase in BAP from 130.38 to 338.67 g and 148.33 to 343.33 g. The use of agricultural alternatives reduced the disease in fruit plants and increased the weight of the almond, which turned out to be an integral management strategy.